STATUS REPRODUKSI DAN ESTIMASI OUTPUT BANGSA-BANGSA KAMBING DI DESA KARANG ENDAH KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH - Sundari Aprilinda; Sulastri ,; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The aim of the study was to identify reproduction status, natural increase, net replacement rate, and output in each goat breeds of Karang Endah village, Terbanggi Besar subdistrict, Lampung Tengah. The research was started in August until September 2015. The results showed that the structure of the goat population in the village of Karang Endah consists of 47 Peranakan Etawah (PE) goats, 225 Rambon goats, and 117 Kacang goats. Reproduction status goat in Karang Endah: PE goat, first mating males and females (13.00 and 13.46 months), post partum mating (2.69 months), calving interval (7.69 months). Rambon goat, first mating males and females (9.13 and 11.67 months), post partum mating (2.49 months), calving interval (7.49 months). Kacang goat, first mating males and females (8.76 and 10.25 months), post partum mating (1.50 months), calving interval (6.50 months). Goats PE natural increase (38.30%), net replacement rate of males and females (668% and 306.38%), output (38.29%). Goats Rambon natural increase (29.33%), net replacement rate of males and females (397% and 179.94%), output (29.33%). Natural increase Kacang goats (27.35%), net replacement rate of males and females (221% and 317.80%), output (27.35%). (Keywords: Population structure, reproduction status, Natural Increase, Net Replacement Rate, Output)